Aplicação dos artigos 521 e 523 do código de processo civil à execução trabalhista face a busca da efetividade da tutela jurisdicional - Andrade, Raphael Dias (2019)
The work in question will seek to analyze the subsidiary use of precepts of the Civil Procedure Code to labor enforcement with verification of its compatibility with the labor procedure and the search for effectiveness in the enforcement actions. This study will also examine whether such a form of subsidiarity will not entail an infringement of the principle of legal certainty, thus analyzing the extent to which it would be feasible to apply the provisions of the Civil Procedure Code to labor enforcement in order to receipt of labor claims, given their alimentary nature. For that, an initial study will be carried out on the gaps and integration’s means of the law, especially in the scope of labor law, also as a form of integration in the labor execution. At the end, it will be verified the feasibility of applying Articles 521 and 523, Civil Procedure Code to the labor process, confronting the procedures of the Labor Justice and Common Justice. It seeks to bring clarification about the split that remains within the scope of the Specialized Justice in relation to the above mentioned precepts, but always focused on its analysis and applicability with compatibility with the principles of effectiveness and legal certainty.